Synthesis and investigation of the electrical properties of novel liquid-crystal phthalocyanines bearing triple branched alkylthia chains - Canimkurbey, Betul; Taskan, Mustafa Can; Demir, Sevde; Duygulu, Ercan; Atilla, Devrim; Yüksel, Fatma (Royal Soc Chemistry, 2020)
The synthesis and electrical characterization, and liquid crystalline and conducting properties of novel peripheral- and non-peripheral-tetra 2-(tri(hexylthio))ethoxy- and 2-(tri(octylthio))ethoxy-substituted copper(ii) phthalocyanines have been reported. The thermal stabilities of the phthalocyanine compounds have been determined by thermogravimetric analysis. The mesogenic properties of these new materials have been investigated by differential scanning calorimetry, polarized optical microscopy and X-ray diffraction measurements. These newly synthesized liquid crystalline materials have been used as the semiconductor layer in organic field effect transistors (OFETs), and OFET characterization has been performed.
Keywords: Field-Effect Transistors; Discotic Mesophases; Metal-Complexes; Behavior; Derivatives; Separation; Alpha